Multidimensional evaluation of scientific inputs and output: A study of Asean / Vignes Gopal Krishna - Vignes, Gopal Krishna (2016)

(untitled)
This thesis analyzed the importance of scientific research through scientific collaboration, social networking sites and journal impact factors. The rapid growth of science, technology and innovation has inspired scientific publications with international collaborators in high impact journals. Social networking sites are useful as a virtual alternative for expanding research opportunities, though some researchers feel that it is more for social communications. Diachronous impact factor has gained attention among diverse agents as a tool to evaluate significance of Institute for Scientific Information’s indexed journals. Most productive researchers in Malaysia chose the collaborators who have the highest number of scientific publications. Significant differences in both rates and strengths of scientific collaborations were observed among most productive authors except for most productive institutions through Kruskal-Wallis test. The rates of scientific collaboration between the local and international institutions have been low because of poor networking ability among local researchers. Lower research visibility would reduce the demand for scientific collaboration. Scientific collaboration between researchers in Malaysia and the ASEAN countries have been low because of limited talents in writing joint papers. Socimetrics and Conversational Analysis have reflected significant research conversations among active participants from Malaysia in Facebook. Researchers from Singapore, Thailand, Vietnam, Indonesia and the other ASEAN member states preferred physical instead of virtual medium for research communications. LinkedIn has pointed out limited research communication between researchers from Singapore and Thailand via Socimetrics and Conversational Analysis. It neglects Brunei, Indonesia, Laos and others from the analysis for revealing limited research participations in LinkedIn. There iv were also Intellectual interactions between Malaysia, Pakistan, India, the USA and Australia in Facebook and LinkedIn through Socimetrics and Conversational Analysis. The most suitable measure for evaluating performing Malaysian journals both in the short-term and long-term is diachronous impact factor based on unique citing sources. It has showed the non-overlapping effects (62 percent) in revealing “true” scientific performance and fairness of the journals through forward approach in Malaysia. In Thailand, the diachronous impact factor, based on unique citing subject categories, took the lead to remove the biasness of classical impact factor. In Philippines, Diachronous impact factors based on citing organizations and unique citing sources have removed the biasness of existing impact factors. Diachronous impact factor based on citation concentration index allows both first-comer and latecomer journals in Economics to improve their scientific visibility in a fairer way. It removes the bias in short-term impact factor. The discussions on scientific collaborations, social networking sites and journal impact factors would allow policymakers to maintain the effective resource allocations.